2009
DOI: 10.1021/ja901718q
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular Repulsion through Interfacial Attraction: Toward Engineering of Polymorphs

Abstract: Understanding the formation of crystalline polymorphs is of importance for various applications of materials science. Polymorphism of Schiff base derivatives has recently attracted considerable attention because of its influence on photochromic and thermochromic properties of their 3D crystals. The present investigation extends the study of Schiff base polymorphism to the molecular level by using a combination of scanning tunneling microscopy at the liquid/solid interface and molecular modeling. It is demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 31 publications
2
38
0
Order By: Relevance
“…A number of experimental parameters have already been identified that control the appearance of a certain type of polymorph over another. A non-comprehensive list of these parameters includes the type of solvent [23][24][25][26][27][28][29], the concentration of molecules [30][31][32][33][34][35], the type of substrate [36][37][38][39][40][41], the temperature at which the self-assembly takes place [42][43][44][45] and the thermal history of the sample [46]. How these parameters affect the self-assembly of organic building blocks is the subject of this review, with a special focus on the liquid-solid interface.…”
Section: Introductionmentioning
confidence: 99%
“…A number of experimental parameters have already been identified that control the appearance of a certain type of polymorph over another. A non-comprehensive list of these parameters includes the type of solvent [23][24][25][26][27][28][29], the concentration of molecules [30][31][32][33][34][35], the type of substrate [36][37][38][39][40][41], the temperature at which the self-assembly takes place [42][43][44][45] and the thermal history of the sample [46]. How these parameters affect the self-assembly of organic building blocks is the subject of this review, with a special focus on the liquid-solid interface.…”
Section: Introductionmentioning
confidence: 99%
“…23 The combination of scanning tunneling microscopy at the liquid-solid interface and molecular modeling has been used to study the formation of polymorphs on gold surfaces, examining the moleculesubstrate interactions that lead to the formation of two-dimensional crystals. 24 Using Schiff base compounds as models for study, it was determined that molecules could self-organize on Au(111) surfaces into columnar and dimer structures, demonstrating that the dimer-based structure was derived from molecule-surface interactions that were capable of modifying molecule-molecule interactions.…”
Section: Studies Of Preparative and Isolation Methodologymentioning
confidence: 99%
“…The synthesis of SA1 was reported in [10], but in our study we used a different synthesis method for this compound. …”
Section: Synthesis Of the Sa1 And Sa2 Compoundsmentioning
confidence: 99%